STUDI TENTANG PEKERJAAN, KADAR HB, DAN KONDISI KESEHATAN IBU SAAT HAMIL DENGAN KONDISI BAYI BARU LAHIR DI KRI NU MADINAH PUJON - Sayuti, Sayuti; Qotimah, Qotimah; Setyowati, Susana (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Normal newborns are babies born with a gestational age of more than or equal to 37 weeks with a weight of 2500-4000 grams. The condition of the mother during pregnancy can affect the condition of the baby at birth, for example, mothers who have anemia, CED, hypertension, mothers with high parity, or due to other diseases can give birth to babies who are LBW. The purpose of this study was to find out about the relationship between work, Hb levels, and the health condition of mothers during pregnancy and the condition of newborns at the NU Madina Pujon Inpatient Clinic. This study uses a quantitative method with a cross-sectional approach. The sample in this study were all mothers giving birth at the NU Madina Pujon Inpatient Clinic, a total of 30 mothers. The results of this study show that simultaneously there is a relationship between work, Hb levels, and the health condition of the mother during pregnancy and the condition of newborns at the Inpatient Clinic which is indicated by the Fh value > Ftable, namely 14.946 > 2.743. Individually there is a significant relationship seen from the value of th> ttable with a significance value of <0.05.